Nutmeg Oil Gel Preparation for Dandruff Treatment - Sudrajat, Susana Elya; Harahap, Elisabeth Dasmareta; Anggreni, Dewi; Renjaan, Maria (Jurnal MedScientiae, 2023)
Dandruff (Pityriasis versicolor) is a superficial cutaneous fungal infection characterizes byhypopigmented or hyperpigmented macules and patches, caused by Malassezia furfur, which has highprevalence in tropical region. Nutmeg oil is one of the natural ingredients rich in chemicals that haveanti-fungal. While ketoconazole is an antifungal drug which effective in the treatment of dandruff(Pityriasis versicolor) most often caused by Malassezia furfur. This study aims to determine theeffectiveness of the gel formulation nutmeg oil in inhibiting the growth of Malassezia fur fur. Gelpreparation were made using carbomer, with the formula F1, F2, F3, F4, dan F5, each using0,5%,1%,2%,3%, dan 4% of nutmeg oil. Furthermore, Sabouraud Dextrose Agar (SDA) is used as amedium for bacteria to breed, and riddled it with cork baurer then instilled 20ul nutmeg oil gelformulation with a concentration of 0.5%, 1%, 2%, 3% and 4% and 2% ketoconazole in each hole.Incubated in an incubator at a temperature of 37 o C for 24-48 hours. Then observing the M.furfur, andmeasured its resistance zone using a caliper. Obtained zone of inhibition on Sabouraud dextrose agarwith nutmeg oil gel formulation of 0.5%, 1%, 2%, 3%, 4% and 2% ketoconazole. 3% ketoconazoleinhibition zone equal to 2% ketoconazole inhibition zone. Nutmeg oil gel formulation at a concentration of 3% has the same effectiveness with 2% ketoconazole in inhibiting the growth ofMalassezia furfur as the etiology of dandruff.